Who Owns the Land? - Hodgson, Gordon W. (ARCTIC, 1988)
The editor shares his views on the creation of an Antarctic-type treaty for the Canadian Arctic Islands with reasonable and shared access for everyone. "By offering Canadian arctic islands and associated waters as a demilitarized international park, say under the control of the United Nations, the Canadian nation would be seen to be taking an enormous step forward on the world scene by dissociating itself from the global arms race and by showing an enlightened and determined leadership never before contemplated in northern latitudes."